Reversible Posterior Leukoencephalopathy Syndrome (RPLS) in Late Onset Postpartum Eclampsia- A Retrospective Study - Vikrant Kanagaraju; B Devanand (Asian Journal of Medical Radiological Research, 2020)
Background: Reversible posterior leukoencephalopathy syndrome (RPLS) or Posterior reversible encephalopathy syndrome (PRES) is a unique clinicoradiologic entity characterized by acute onset headache, seizures, blindness and altered mental state associated with reversible vasogenic edema of the brain. It is a major complication of eclampsia, but data on clinicoradiological features of PRES in late-onset postpartum eclampsia are scarce. The objective is to analyze the clinicoradiologic features and outcome in a cohort of late postpartum eclampsia patients with PRES. Subjects and Methods: Eighteen patients of late postpartum eclampsia with clinical as well as neuroimaging features consistent with PRES were included in this retrospective study. All had undergone magnetic resonance imaging (MRI) with diffusion-weighted imaging (DWI) and apparent diffusion coefficient(ADC) mapping. Data on age, antepartum history, peak systolic and diastolic blood pressures, clinical features, time to neuroimaging, location of lesions on brain imaging and presence of associated ischemia or hemorrhage in MRI were collected and analyzed. Results: The mean age was 25.72 3.23 years. The average duration between labor and clinical symptoms was 8.5 days. 13/18 patients (72.2%) had elevated blood pressure at admission. Mean systolic and diastolic blood pressures were 143.88 (120-180) and 93.88 (80-100) mm Hg respectively. Headache was the presenting feature in 16 patients. The parieto-occipital regions were the most frequently involved followed by the cerebellum (7/18) and frontal lobe (4/18). Atypical regions were not involved. Clinical recovery had been noted in all. Conclusion: PRES associated with late postpartum eclampsia, an entity of limited awareness can present without antecedent preeclampsia. Radiological changes are the key to early diagnosis.